Harvest is - Steinke, T. L., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes the EPA's definition of harvest.
CEPEP 05/04, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides -- Labeling; Agricultural chemicals -- Government policy; Pesticides -- Colorado -- Safety measures